Tribute to Alexei Borisovich Kaidalov. (April 2015) - Merino, C
Abstract: The author wrote these lines to recollect some personal memories of Alexei Borisovich Kaidalov and of the collaboration the author carried out with him under his guidance for almost 20 years. By doing so the author has once again confirmed the realization of the deep influence that Alexei Borisovich and his contribution to physics had and still has in the spirit of the author, and in the formation of several generations of physicists, both from Russia and from abroad.